Optical Excitation of Ultra‐Relativistic Partially Stripped Ions. Issue 3 (12th February 2022) - Bieroń, Jacek; Krasny, Mieczyslaw Witold; Płaczek, Wiesław; Pustelny, Szymon
Abstract: The Gamma Factory (GF) initiative aims at the construction of a unique experimental tool exploiting resonant interaction of light with ultra‐relativistic partially stripped ions (PSI) stored in circular accelerators at CERN. Resonant excitation of high‐energy electronic transitions in the ions is achieved through Doppler‐boosting (by twice the Lorentz factor; from hundred to several thousand times) of light energy. In order to efficiently excite the ions, and hence generate intense beams of scattered/fluorescent photons, a detailed knowledge of the ions' electronic energy structure and the dynamics of optical excitation is required. Spectroscopic properties of PSI selected for the GF operation, as well as their optical excitation schemes, are investigated. Two regimes of the ion–light interaction are identified, leading to different dynamics of the excitation. The efficiency of the ion–light interaction, as well as the number of photons emitted from a single ion bunch, are estimated, both analytically and numerically, for three ions considered for the GF, that is,  Li‐like 0 82 208 ${}^{208}_{\phantom{0}82}$ Pb 79 +, Li‐like 20 40 ${}^{40}_{20}$ Ca 17 +, and H‐like 0 82 208 ${}^{208}_{\phantom{0}82}$ Pb 81 + . Abstract : Implementation of the Gamma Factory (GF) requires identification of ions to be accelerated and stored. It also necessitates development of schemes of ions' efficient excitation. Here, the first systematic studies of the most promising candidates and excitation schemes are presented, providing realistic estimates of energy and flux of GF‐emitted photons.